Meteorus obsoletus - Stigenberg, Julia; Ronquist, Fredrik (Zenodo, 2011)
Meteorus obsoletus (Wesmael) Fig. 113 Perilitus obsoletus Wesmael, 1835:49. Lectotype ♀, Belgium: Brussels, coll Wesmael (IRSNB, Brussels). Meteorus viridane Johansson, 1964:251. Holotype ♀, Sweden: Borgholm, 30.vi.1954, ex larva of Tortrix viridanae (L.) coll. 13 –16.vi.1954 (Johansson) (MZLU, Lund) synonymized by Huddleston, 1980:42 —examined Diagnosis : Meteorus obsoletus is very similar to M. versicolor . The best diagnostic characters to separate these species are the length and shape of the ovipositor (slender and long, 2.0–2.5 times petiolar tergum in the former; stouter, 1.5–2.0 times petiolar tergum in the latter), the shape of the eyes (not so protruding in the former, strongly protruding in the latter) and the temple (longer and more rounded in the former, more contracted in the latter). Studied material : ~ 10 specimens. Description : Size about 3.5–4mm. Antennal articles 27–30. Head rounded behind eyes. Ocelli large, OOL=OD. Eyes not protuberant, slightly convergent. Clypeus slightly protuberant. Tentorial pits small and shallow. Mandibles small, strongly twisted. Precoxal sulcus reticulate-rugose. Propodeum rounded with a weak medial impression posteriorly, irregularly reticulate-rugose. Petiolar tergum slender, finely longitudinally striate dorsally, without dorsal pits. Ovipositor 2.0–2.5 times length of petiolar tergum, straight and slender. Hind coxa smooth, tarsal claws with strong basal lobe. Colour brownish black; head, prothorax, legs, mesothorax and abdomen usually testaceous. Male same as female except eyes and ocelli smaller. Distribution : Palearctic. Country records: Austria; Belgium; Bulgaria; Czechoslovakia; France; Germany; Ireland; Italy; Japan; Korea; Moldova; Netherlands; Sweden; Switzerland; Turkey; Ukraine; United Kingdom; Yugoslavia. Biology : We found one specimen within the SMTP. It was caught in the middle of July in an old spruce forest. Host records of M. obsoletus include four different Lepidoptera families, but the predominant hosts appear to belong to the family Tortricidae. In Japan they were found on the species Choristoneura diversana (Tortricidae) and Huddleston (1980) also mentions the species Tortrix viridana and Gypsonoma dealbana (Tortricidae). : Published as part of Stigenberg, Julia & Ronquist, Fredrik, 2011, Revision of the Western Palearctic Meteorini (Hymenoptera, Braconidae), with a molecular characterization of hidden Fennoscandian species diversity 3084, pp. 1-95 in Zootaxa 3084 (1) on page 63, DOI: 10.11646/zootaxa.3084.1.1, http://zenodo.org/record/5244448 : {"references": ["Wesmael, C. (1835) Monographie des Braconides de Belgique. Nouveaux Memoires de l'Academie Royales des Science. Bruxelles, 9, 1 - 252.", "Huddleston, T. (1980) A revision of the Western Palaearctic species of the genus Meteorus (Hymenoptera: Braconidae). Bulletin of the British Museum (Natural History), Entomology series, 41, 1 - 58."]}